(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify the reality of using Artificial Intelligence (AI) in scientific research and the ethical responsibility among students of the Chemistry Department at the College of Education for Pure Sciences, University of Diyala. The research community consisted of (163) male and female students from the fourth stage of the Chemistry Department ،The research sample consisted of (62) male and female fourth-year students, and the researcher adopted a descriptive research methodology due to its alignment with the research problem and objectives. The researcher developed two research instruments: the first was a scale to measure the reality of AI usage consisting of two domains with a total of (20) items, where the first domain represents the extent of AI usage in scientific research (10 items) and the second domain addresses the difficulties of using AI in scientific research (10 items). The second instrument was an ethical responsibility scale comprising four domains (data privacy, transparency in information use, scientific integrity, and plagiarism) with a total of (16) items, four for each domain, utilizing a five-point Likert scale for both instruments. The researcher established both face and content validity and used Cornbrash’s alpha to measure reliability, which reached (0.91) for the first scale and (0.93) for the second scale. The results indicated that the extent of using AI tools was "high" with a weighted mean of (3.51), and the difficulties encountered also ranked "high" with a weighted mean of (3.54), while ethical responsibility regarding AI use in scientific research was "high" with a weighted mean of (3.93). In light of these results, the researcher offered several recommendations, including the necessity of using AI in scientific research and overcoming the obstacles students face, as well as emphasizing students’ commitment to ethical responsibility when preparing scientific research. The researcher also suggested conducting similar studies for other academic subjects and higher education levels (Master’s and Doctorate).